Effects of African oil palm monocrops in the role of small mammals within the transmission cycle of Trypanosoma cruzi (2018)
Chagas disease, caused by the parasite Trypanosoma cruzi, is one of the most prevalent vectorborne diseases in Latin America. Human intervention in wild habitats can alter the transmission cycle of the parasite by the modification of interactions between vectors and hosts. This could be the case of African oil palm (Elaeis guineensis) cultivation in Colombia, given the reports of infestation of these monocrops by the vector Rhodnius prolixus. We aim to evaluate the possible effect of human intervention in the transmission of Chagas disease, by developing an epidemiological model that allow us to describe the infection dynamics of wild small mammals in two habitats with different land use in Casanare. Overall infection of collected individuals was significantly higher in the native Attalea butyracea forest (18.4%) compared to infection in the plantation (6.2%); being Rodentia order the only one to exhibit a significant difference (18.92% in forest vs. 3% in plantation). Prevalence in Didelphimorphia was 16% and 0%, while Chiroptera individuals exhibit 20% and 11% infection percentages. Model estimates a higher predation activity in the forest, increasing the risk of oral transmission of the parasite. Furthermore, is estimated that vectors in the plantation have higher probability of infection, presumably due to the higher parasitemia that species found in this habitat can reach. Here we show evidence of establishment of African oil palm plantations in Casanare as a risk factor for Chagas disease transmission, by promoting vector infestation of new scenarios and by increasing the number of susceptible and highly infective hosts.